Substrate-bound and soluble domains of tenascin-C regulate differentiation, proliferation and migration of neural stem and progenitor cells - Glotzbach, Kristin; Faissner, Andreas (Frontiers in Cellular Neuroscience, 2024)
The lack of regenerative capacity of the central nervous system is one of the major challenges nowadays. The knowledge of guidance cues that trigger differentiation, proliferation and migration of neural stem and progenitor cells is one key element in regenerative medicine. The extracellular matrix protein tenascin-C (Tnc) is a promising candidate to regulate cell fate due to its expression in the developing central nervous system and in the adult neural stem cell niches. Of special interest are the alternatively spliced fibronectin type III (FnIII) domains of Tnc whose combinatorial diversity could theoretically generate up to 64 isoforms in the mouse. 27 isoforms have been discovered in the developing brain, among others the domain combinations A1D, CD and A124BCD. These domains as well as the combination of the constitutively expressed FnIII domains 7 and 8 (78) were expressed in Chinese hamster ovary cells as pseudo-antibodies fused to the Fc-fragment of a human immunoglobulin G antibody. The fusion proteins were presented to primary mouse neural stem/progenitor cells (NSPCs) grown as neurospheres, either as coated culture substrates or as soluble additives in vitro. We analyzed the differentiation, proliferation and migration of NSPCs and observed that the domain combination A124BCD promoted the differentiation of neurons and oligodendrocytes, whereas the domain A1D supported astrocyte differentiation. The constitutively expressed domain 78 had a proliferation and migration stimulating impact. Moreover, most effects were seen only in one of the presentation modes but not in both, suggesting different effects of the Tnc-domains in two-and three-dimensional cultures. Artificial hydrogels spiked with Tnc-domains assembled in a three-dimensional culture might represent a promising tool in regenerative medicine.